Effects of CO2 and iron availability on phytoplankton and eubacterial community compositions in the northwest subarctic Pacific. - Endo, H; Yoshimura, T; Kataoka, Takafumi; Suzuki, Koji (PANGAEA, 2013)
On-deck CO2-Fe-manipulated incubation experiments were conducted using surface seawater collected from the Western Subarctic Gyre of the NW Pacific in the summer of 2008 to elucidate the impacts of ocean acidification and Fe enrichment on the abundance and community composition of phytoplankton and eubacteria in the study area. During the incubation, excluding the initial period, the mean partial pressures of CO2 in non-Fe-added bottles were 230, 419, 843, and 1124 µatm, whereas those in Fe-added treatments were 152, 394, 791, and 1008 µatm. Changes in the abundance and community composition of phytoplankton were estimated using HPLC pigment signatures with the program CHEMTAX and flow cytometry. A DGGE fingerprint technique targeting 16S rRNA gene fragments was also used to estimate changes in eubacterial phylotypes during incubation. The Fe addition induced diatom blooms, and subsequently stimulated the growth of heterotrophic bacteria such as Roseobacter, Phaeobacter, and Alteromonas in the post-bloom phase. In both the Fe-limited and Fe-replete treatments, concentrations of 19'-hexanoyloxyfucoxanthin, a haptophyte marker, and the cell abundance of coccolithophores decreased at higher CO2 levels (750 and 1000 ppm), whereas diatoms exhibited little response to the changes in CO2 availability. The abundances of Synechococcus and small eukaryotic phytoplankton (<10 µm) increased at the higher CO2 levels. DGGE band positions revealed that Methylobacterium of Alphaproteobacteria occurred solely at lower CO2 levels (180 and 380 ppm) during the post-bloom phase. These results suggest that increases in CO2 level could affect not only the community composition of phytoplankton but also that of eubacteria. As these microorganisms play critical roles in the biological carbon pump and microbial loop, our results indicate that the progression of ocean acidification can alter the biogeochemical processes in the study area.
Seawater carbonate chemistry and phytoplankton and eubacterial community compositions in the northwest subarctic Pacific
Keywords: 19-hexanoyloxyfucoxanthin, growth; 19-Hexanoyloxyfucoxanthin, growth, standard deviation; Alkalinity, total; Aragonite saturation state; Autoanalyzer; Bacteria, heterotrophic; Bacteria, heterotrophic, standard deviation; Bicarbonate ion; Bottles or small containers/Aquaria ( 20 L); Calcite saturation state; Carbon, inorganic, dissolved; Carbonate ion; Carbonate system computation flag; Carbon dioxide; CHEMTAX (Lewitus et al., 2005); Chlorophyll a; Chlorophyll a, standard deviation; Chlorophytes; Community composition and diversity; Coulometric titration; Cryptophytes; Cyanobacteria; DEPTH, water; Diatoms; Dinophytes; Entire community; Fucoxanthin, growth; Fucoxanthin, growth, standard deviation; Fugacity of carbon dioxide (water) at sea surface temperature (wet air); Haptophytes; High Performance Liquid Chromatography (HPLC); Incubation duration; Laboratory experiment; Maximum photochemical quantum yield of photosystem II; Maximum photochemical quantum yield of photosystem II, standard deviation; Micro-nutrients; Nitrate; Nitrogen/Phosphorus uptake ratio; Nitrogen/Phosphorus uptake ratio, standard deviation; North Atlantic; North Pacific; OA-ICC; Ocean Acidification International Coordination Centre; Open ocean; PAM (PhytoPAM, Phyto-ED Walz, PPAA0138); Partial pressure of carbon dioxide (water) at sea surface temperature (wet air); Pelagophytes; Pelagos; pH; Phosphate; Pigments, Turner fluorometer; Potentiometric titration; Prasinophytes; Primary production/Photosynthesis; Salinity; Silicate; Silicon/Nitrogen uptake ratio; Silicon/Nitrogen uptake ratio, standard deviation; Synechococcus spp.; Synechococcus spp., standard deviation; Temperate; Temperature, water; Treatment; Ultraphytoplankton, eukaryptic; Ultraphytoplankton, eukaryptic, standard deviation; Water sample; WS; WSG_water